REVIEW: MARKET, CAPITAL, AND FOREIGN LABOR ACCESS FOR ALL THAI FARMERS - Tanielian, Adam; Kampan, Palapan (Asian Journal of Agriculture, 2020)
Abstract. Tanielian A. 2020. Review: Market, capital, and foreign labor access for all Thai farmers. Asian J Agric 3: 41-59. A quantitative study of agricultural economic indicators for Thailand, its provinces, and seventeen other countries show Thailand's agriculture sector desperately needs assistance to lift farmers out of poverty and Thailand out of the middle-income trap. Data shows diminishing activity in the agricultural sector may be harming productivity and growth. Prices and yields plateau and fall as producer costs increase and farm incomes remain among the lowest. In 2006 and 2014, the military ousted two Shinawatra Prime Ministers amid corruption and misappropriation scandals relating to failed agricultural subsidy schemes that cost the government billions of dollars while failing to substantially improve the situations of millions of smallholder farmers throughout the Kingdom. Analysis of primary data and literature suggest Thai farmers lack sufficient access to labor, capital, and markets that would give them the resources to improve farming methods, hire short-term labor, and ultimately rise in socioeconomic status along with the rest of the population. Recommendations include a series of government-sponsored and joint public-private initiatives that organize farmers into unions and connect them with human, financial, scientific, market, and educational resources via a range of mobile applications.